Evaluating the Impact of Rapid Thermoresistance (RTT) on Membrane and Chromatin Features in Post-Thawed Bovine Semen (Global Journal of Medical Research, 2024)
This work aims to evaluate the effects of rapid thermoresistance on the morphofunctional aspects of membranes using flow cytometry as well as the quality of sperm chromatin using the Toluidine Blue technique both before and after the thermoresistance test Six sets of frozen semen from ten bulls were used The samples were thawed in a water bath at 36 C and separated into two aliquots The first aliquot control group C was kept in a test tube previously heated to 36 C with subsequent evaluationsusingmicroscopy cytometry and chromatin analyses The second aliquot experimental group E underwent the rapid thermoresistance test RTT in a water bath preheated at 46 C for 30 minutes with subsequent evaluations usingmicroscopy cytometry and chromatin analyses For statistical analysis the paired T test significance P 0 05 was used It was observed that from the results presented semen samples after the resistance test showed a reduction of approximately 56 for motility and 36 for vigor P 0 05 when compared to samples before the test
Keywords: fertility; membranes; sperm cells; thermoresistance